Population structure, genetic diversity and evolutionary history of the narrow endemic squirrel Sciurus meridionalis - Roberta Bisconti; Andrea Chiocchio; Adriana Bellati; Gaetano Aloise; Daniele Canestrelli (Global Ecology and Conservation, 2024)
Endemic species and their genetic diversity are critical components of global biodiversity, yet they usually face a higher risk of decline and extinction than species with broader distributions. Loss of genetic diversity within geographically restricted and fragmented ranges plays a significant role in driving endemic species to extinction, threatening their ability to adapt to environmental challenges. Hence, considering genetic diversity and its spatial distribution within populations is mandatory in planning conservation actions for narrow endemic species. Here, we investigated the population genetic diversity, structure and evolutionary history of the Calabrian black squirrel Sciurus meridionalis, a species endemic to the Calabrian region in the south of the Italian peninsula. A fine-scale sampling procedure was carried out throughout the whole species range, and genetic variation was assessed from multiple mitochondrial and nuclear markers. Phylogeographic and population structure analyses showed three evolutionary significant units within the current species range, each characterised by extremely low levels of genetic diversity. Bayesian phylogeographic analyses suggested that Calabrian black squirrel populations experienced a range fragmentation during the Last Glacial Maximum (∼20 ka), which geographically mirrors the three main mountain massifs within the species range. Historical demographic reconstructions revealed a recent and still ongoing demographic expansion for Calabrian black squirrel populations, likely promoted by a concurrent expansion of the Calabrian black pine in this area. Overall, our findings clarify the designation of the evolutionary significant units for a narrow endemic squirrel and underscore the importance of analysing range-wide population genetic data and considering species interactions when defining management strategies for narrow endemic species’ conservation.